Abundance and Significance of Neuroligin-1 and Neurexin II in the Enteric Nervous System of Embryonic Rats. (18th January 2017) - Wang, Dongming; Pan, Jingnian; Song, Guoxin; Gao, Ni; Zheng, Yi; Zhang, Qiangye; Li, Aiwu
Abstract : Aim . To investigate the abundance of neuroligin-1 and neurexin II in the enteric nervous system (ENS) of rats on different embryonic days and to explore their potential significance. Methods . The full-thickness colon specimens proximal to the ileocecal junction of rats on embryonic days 16, 18, and 20 and of newborns within 24 hours (E16, E18, E20, and Ep0) were studied, respectively. qRT-PCR was applied for detecting the expressions of neuroligin-1 and neurexin II on mRNA, and western blotting was employed for detecting their further expressions on the whole tissue. Finally, the histological appearance of neuroligin-1 and neurexin II α was elucidated using immunohistochemical staining. Results . qRT-PCR showed that the neuroligin-1 and neurexin II mRNA expressions of groups E16, E18, E20, and Ep0 increased gradually with the growth of embryonic rats (P < 0.05 ). Western blotting confirmed the increasing tendency. In immunohistochemical staining, proteins neuroligin-1 and neurexin II α positive cells concentrated mostly in the myenteric nerve plexus of the colon and their expressions depend on the embryonic time. Conclusion . Neuroligin-1 and neurexin II were both expressed in the ENS and have temporal correlation with the development of ENS, during which neuronal intestinal malformations (NIM) may occur due to their disruptions and consequent abnormal ENS development.